2008
DOI: 10.1186/1471-213x-8-115
|View full text |Cite
|
Sign up to set email alerts
|

RBM19 is essential for preimplantation development in the mouse

Abstract: BackgroundRNA-binding motif protein 19 (RBM19, NCBI Accession # NP_083038) is a conserved nucleolar protein containing 6 conserved RNA recognition motifs. Its biochemical function is to process rRNA for ribosome biogenesis, and it has been shown to play a role in digestive organ development in zebrafish. Here we analyzed the role of RBM19 during mouse embryonic development by generating mice containing a mutation in the Rbm19 locus via gene-trap insertion.ResultsHomozygous mutant embryos failed to develop beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
2
22
1
Order By: Relevance
“…Previous studies have shown that p53 activation and subsequent induction of apoptosis is common when ribosome biogenesis and translation are disrupted (Azuma et al, 2006;Chakraborty et al, 2009;Danilova et al, 2010;Skarie and Link, 2008;Zhang et al, 2003Zhang et al, , 2008. Our and previous results show, however, that the direct contribution of p53 activation to the reduced health of the mutant retina appears to be small.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies have shown that p53 activation and subsequent induction of apoptosis is common when ribosome biogenesis and translation are disrupted (Azuma et al, 2006;Chakraborty et al, 2009;Danilova et al, 2010;Skarie and Link, 2008;Zhang et al, 2003Zhang et al, , 2008. Our and previous results show, however, that the direct contribution of p53 activation to the reduced health of the mutant retina appears to be small.…”
Section: Discussioncontrasting
confidence: 82%
“…59 Furthermore, inactivation of RNA binding motif protein 19 (Rpm19) in the mouse triggers apoptosis in the morula stage of the developing embryo, subsequently terminating further development. 60 Collectively, these data support the notion that inappropriate accumulation of mature rRNA, via the disruption of appropriate rRNA precursor processing, is sufficient to signal a stress response to p53 that may derive from the RP-Mdm2 pathway.…”
Section: Monographssupporting
confidence: 61%
“…Further, disruption of Wrd12, a binding partner of Bop1, has been shown to render similar effects on the cell cycle by activating p53, specifically in an ARF-independent manner, suggesting that an ribosomal protein–MDM2–p53 pathway may mediate this response (Sugimoto et al 2003; Holzel et al 2005). Deficiency of other processing factors like RNA-binding motif protein Rbm19 in mice disrupts embryonic development in a manner dependent on p53-induced apoptosis (Zhang et al 2008). In addition, depletion of Wrd36 in zebrafish perturbs 18S rRNA processing to induce p53-dependent activity (Skarie and Link 2008).…”
Section: P53 Surveillance Of Nucleolar Stressmentioning
confidence: 99%